BUSINESS INTELLIGENCE STRATEGY TO SUPPORT BUSINESS DECISIONS - Anak Agung Gede Ajusta,; Wawan Ridwan,; Eni Reptiningsih,; Nanang Lidwan, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The rapid advancement of information technology has significantly increased the importance of Business Intelligence (BI) systems in supporting more accurate and effective business decision-making processes. This paper aims to examine the role and strategies of BI in enhancing the quality of business decisions, focusing on the application of BI in processing large data sets to generate relevant insights. Using a descriptive analysis approach, this paper explores key components of BI strategies, including data warehousing, data analysis, and real-time reporting accessible to managers and decision-makers. The study also discusses challenges faced by companies in implementing BI, such as data integration issues, costs, and the need for adequate technical skills. Furthermore, the paper highlights the long-term benefits of using BI, including improved operational efficiency, reduced risks, and enhanced competitiveness. In conclusion, an effective BI strategy can provide companies with a significant competitive advantage by supporting data-driven decisions that are more accurate and relevant